Comparative effects of lymphatic drainage and soft tissue mobilization on pain threshold, shoulder mobility and quality of life in patients with axillary web syndrome after mastectomy - Tahniyat Amir Meer; Rabiya Noor; Muhammad Salman Bashir; Mehwish Ikram (BMC Women's Health, 2023)
Abstract Purpose The purpose was to compare the effects of manual lymphatic drainage and soft tissue mobilization on pain threshold, shoulder mobility and quality of life in patients with axillary web syndrome. Methods This randomized clinical trial was conducted on 36 breast cancer patients with developed axillary web; participants were randomly divided into two groups. One group was treated with manual lymphatic drainage; the other group was treated with soft tissue mobilizations in addition to therapeutic exercises, i.e., stretching, strengthening and range of motion (ROM) exercises. The duration of treatment was four weeks (5 sessions/week), with therapeutic exercises as a common treatment protocol. Outcome measures were Breast-Cancer specific quality of life questionnaires, Disabilities of the Arm, Shoulder and Hand (DASH), Numeric Pain Rating Scale (NPRS), Patient Specific Functional Scale (PSFS), Dynamometer and Goniometer. All outcome measure readings were recorded at baseline and the end (4th week) of the treatment. Results The compliance of the variable distribution with normal distribution was verified using the Shaphiro-Wilk test. Parametric tests were applied, and both groups showed significant effects (p < 0.05) in pairwise comparison (paired t-test). The comparison group analysis (independent t-test) showed that there was no significant difference in pain, upper limb strength, range of motions and fatigue component of quality of life questionnaire parameters (p > 0.05). Two parameters (DASH, PSFS) and one component of the quality of life questionnaire (global health) showed a significant difference (p < 0.05). Conclusion Manual lymphatic drainage showed more improvement in functional movements. It was concluded that both groups, manual lymphatic drainage and soft tissue mobilization groups were clinically equally effective. Trial Registration Number This trial is registered at ClinicalTrial.gov PRS under trial number NCT05463185 on date 18/07/2022.